2014
DOI: 10.1098/rspb.2014.1796
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning the net effect of host diversity on an emerging amphibian pathogen

Abstract: The 'dilution effect' (DE) hypothesis predicts that diverse host communities will show reduced disease. The underlying causes of pathogen dilution are complex, because they involve non-additive (driven by host interactions and differential habitat use) and additive (controlled by host species composition) mechanisms. Here, we used measures of complementarity and selection traditionally employed in the field of biodiversity-ecosystem function (BEF) to quantify the net effect of host diversity on disease dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
87
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 54 publications
0
87
0
Order By: Relevance
“…Biodiversity is widely acknowledged to significantly influence the magnitude and stability of a large array of ecosystem properties, with stronger impacts evident when larger scales (1) and multiple functions are considered (2,3). These findings provide compelling support for biodiverse systems being functionally robust, with greater stability of function (4)(5)(6), resistance to invasion (7)(8)(9)(10), and resistance to pathogen spread (11). Some of the impacts of higher levels of biodiversity on ecosystem properties that are apparent at ecological timescales (e.g., greater resistance to invasion) may influence evolutionary processes, like extinction rates.…”
mentioning
confidence: 64%
“…Biodiversity is widely acknowledged to significantly influence the magnitude and stability of a large array of ecosystem properties, with stronger impacts evident when larger scales (1) and multiple functions are considered (2,3). These findings provide compelling support for biodiverse systems being functionally robust, with greater stability of function (4)(5)(6), resistance to invasion (7)(8)(9)(10), and resistance to pathogen spread (11). Some of the impacts of higher levels of biodiversity on ecosystem properties that are apparent at ecological timescales (e.g., greater resistance to invasion) may influence evolutionary processes, like extinction rates.…”
mentioning
confidence: 64%
“…In the decades to follow, extensive research on many of the surviving species has confirmed the role of Bd in contributing to population declines across Australia [27], and has shown how species-specific differences in ecology and behaviour contribute to variation in disease dynamics [14,28]. Despite continued declines in many species [25], others have developed ways to persist with infection. Retallick et al [29] described a population of Taudactylus eungellensis persisting with stable infections that had experienced an epidemic die-off 10 years earlier.…”
Section: Impacts Of Chytrid On Amphibian Populations (A) Chytrids As mentioning
confidence: 99%
“…Bd infects over 700 species [6], which means that potentially all species of amphibians can serve as host, vector or reservoir. Laboratory studies have shown that the species composition of tadpole communities affects disease transmission [24,25] as do studies of artificial adult communities [25]. In these cases, some species reduced infection in co-occurring species.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, North American ranids (another species-rich family) that are dependent on water bodies (i.e. lentic habitats) for laying eggs and tadpole development seem to be more prone to Bd infection than strictly terrestrial or directdevelopment species (see also Becker et al 2014).…”
Section: Discussionmentioning
confidence: 99%